PENERAPAN TEORI BELAJAR DAVID KOLB DALAM PEMBELAJARAN MATEMATIKA MATERI KOORDINAT KARTESIUS - Zulfikar Rafi Nurcahyandi; Jayanti Putri Purwaningrum (Universitas Muhammadiyah Makassar, 2022)
David Kolb’s learning theory called Experiential Learning Theory states that learning is not just listening, but reflecting on what has been learned. That learning process can be carried out well if students can understand the material that has been studied by being directly involved in the proving process. Especially in mathematics. Mathematics is still a subject that is not liked by students. Students assume that mathematics is a rote science and it is difficult for them to solve mathematical problems. Therefore, in this article, it will be explained related to David Kolb’s learning theory an its applicationto mathematics learning in Cartesian coordinates. The research method used in the preparation of this article is a literature study on David Kolb’s learning theory and its application to mathematics learning in cartesian coordinates. Experiential learning is carried out through 4 stages, that is 1) concrete experience (feeling), 2) refelection observation (watching), 3) abstract conceptualization (thinking), and 4) active experimentation (doing). Kolb also explained that there are 4 different learning style, that is 1) diverger, 2) assimilator, 3) converger, and 4) accommodator